2003
DOI: 10.2176/nmc.43.457
|View full text |Cite
|
Sign up to set email alerts
|

Subthalamic Nucleus Tumor Causing Hyperphagia-Case Report-

Abstract: A 42-year-old woman with locally advanced breast cancer developed headache just after completing adjuvant chemotherapy. Magnetic resonance imaging revealed a mass located in the left subthalamic nucleus (STN) and involving the posterior part of the thalamus and the hypothalamus. The patient refused a radiologically guided biopsy and gamma knife treatment was not financially possible. Palliative whole brain radiotherapy with hormonal therapy was administered. The patient gained 19 kg body weight during 4 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Furthermore, we have also shown that STN lesions increase motivation for food reward (Baunez et al, 2002, 2005). In PD patients with STN deep brain stimulation, several cases have been reported to show excessive or impulsive behaviour towards food leading to a weight gain, as well as after STN tumour growth (Barutca et al, 2003; Macia et al, 2004). We have previously shown that STN lesions increase motivation for food, while decreasing motivation for cocaine, suggestive of a dissociation of motivational processes between natural reward vs. drugs of misuse (Baunez et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we have also shown that STN lesions increase motivation for food reward (Baunez et al, 2002, 2005). In PD patients with STN deep brain stimulation, several cases have been reported to show excessive or impulsive behaviour towards food leading to a weight gain, as well as after STN tumour growth (Barutca et al, 2003; Macia et al, 2004). We have previously shown that STN lesions increase motivation for food, while decreasing motivation for cocaine, suggestive of a dissociation of motivational processes between natural reward vs. drugs of misuse (Baunez et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…This deficit may indicate an increase in motivation for the reward. In addition, clinical reports showed that an infarct or tumor in the STN could lead to pathology such as hyperphagia, hypersexuality, and mood exaltation (Trillet et al, 1995; Absher et al, 2000; Barutca et al, 2003). Taken together, these data suggest that the STN may be implicated in motivation.…”
Section: Stn In Motivational Processesmentioning
confidence: 99%
“…As DBS inhibits the activity of STN neurons [1,2,18], the weight gain following STN DBS in PD patients may be associated with the inhibition of STN neurons. Consistent with this notion, increased motivation for food intake has been reported in patients with strokes or tumors involving the STN [19,20] and in rats subjected to STN lesions [21,22]. In fact, STN DBS is unable to selectively regulate STN neurons while leaving neighboring axons unperturbed, and both physical and chemical lesions of the STN may cause neuroadaptation.…”
Section: Introductionmentioning
confidence: 61%